A Chinese 'High-Tech Theme Park Full of Stories': Exploring Fantawild Oriental Heritage. Issue 2 (September 2022) - Baker, Carissa
Abstract : Among the Chinese companies that run the great majority of theme parks in China, Fantawild is the quickest-expanding one, with more than two dozen full-fledged theme parks and many in development. The newest of their three primary theme park models, Oriental Heritage, employs traditional Chinese cultural material and specifically Chinese folklore and legends for its attractions and shows. The park thus differentiates itself not only from Fangte's previous park models, Adventure and Dreamland, which have often been derivative of other, Western park themes and ride systems, but also from the glocalizing approaches of such Western companies as Disney or Universal. Combining Chinese stories and heritage with new and innovative ride systems, Oriental Heritage also differs markedly from the 'ethnic culture parks' whose performative open-air displays dominated the first boom phase of the theme park in China during the mid-1990s. With its traditional Chinese architectural style, Chinese intellectual property or cultural traditions, and technically ambitious ride systems, the 'high-tech theme park full of stories', as it refers to itself, marks the culmination of Fangte's brand evolution from the imitative Adventure and Dreamland models to the confidently Chinese Oriental Heritage concept, making Fangte a particularly interesting and potentially representative model of where the Chinese theme park industry could be headed.